Polyphenolic Extracts from Olea europea L. Protect Against Cytokine-Induced beta-Cell Damage Through Maintenance of Redox Homeostasis - KARTAL, MURAT; Cumaoglu, Ahmet; Ari, Nuray; Kartal, MURAT; Karasu, Cimen (My University, 2011)
Various pancreatic beta-cell stressors, including cytokines, are known to induce oxidative stress, resulting in apoptotic/necrotic cell death and inhibition of insulin secretion. Traditionally, olive leaves or fruits are used for treating diabetes, but the cellular mechanism(s) of their effects are not known. We examined the effects of Olea europea L. (olive) leaf and fruit extracts and their component oleuropein on cytokine-induced beta-cell toxicity. INS-1, an insulin-producing beta-cell line, was preincubated with or without increasing concentrations of olive leaf or fruit extract or oleuropein for 24 hr followed by exposure to a cytokine cocktail containing 0.15 ng/mL interleukin-1 beta (IL-1 beta), 1 ng/mL interferon-gamma (IFN-gamma), and 1 ng/mL tumor necrosis factor-alpha (TNF-alpha) for 6 hr. The cytotoxicity was assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) testing. Apoptosis was quantified by detecting acridine orange/ethidium bromide-stained condensed nuclei under a fluorescent microscope. The cells exposed to cytokines had a higher apoptotic rate, a decreased viability (MTT), and an increased caspase 3/7 activity. Both extracts and oleuropein partially increased the proportion of living cells and improved the viability of cells after cytokines. The protective effects of extracts on live cell viability were mediated through the suppression of caspase 3/7 activity. Oleuropein did not decrease the amount of both apoptotic and necrotic cells, whereas extracts significantly protected cells against cytokine-induced death. Cytokines led to an increase in reactive oxygen species (ROS) generation and inhibited glutathione level, superoxide dismutase activity, and insulin secretion in INS-1. Insulin secretion was almost completely protected by leaf extract, but was partially affected by fruit extract or oleuropein. Neither cytokines nor olive derivatives had a significant effect on cellular cytochrome c release and catalase activity. Moreover, the cells incubated with each extract or oleuropein showed a significant reduction in cytokine-induced ROS production and ameliorated abnormal antioxidant defense. The molecular mechanism by which olive polyphenols inhibit cytokine-mediated beta-cell toxicity appears to be involving the maintenance of redox homeostasis.